Pharmacological Inhibition of Glutaminase 1 Normalized the Metabolic State and CD4+ T Cell Response in Sjogren’s Syndrome - Jiayao Fu; Yiping Pu; Baoli Wang; Hui Li; Xiujuan Yang; Lisong Xie; Huan Shi; Zhijun Wang; Junhao Yin; Tianle Zhan; Yanxiong Shao; Changyu Chen; et al. (Journal of Immunology Research)
Previous studies have shown that abnormal metabolic reprogramming in CD4+ T cells could explain the occurrence of several autoimmune disorders, including Sjogren’s syndrome (SS). However, therapeutic targets of the abnormal metabolism of CD4+ T cells remain to be explored. Here, we report that glutaminase 1 (Gls1), a pivotal factor in glutaminolysis, might be involved in the pathogenesis of SS. The expression of Gls1 was upregulated in infiltrated labial CD4+ T cells and circulating CD4+ T cells of SS patients. Inhibiting Gls1 with BPTES significantly abolished the proliferation rate, as indicated by EdU, CFSE, and Western blot analyses. Additionally, BPTES downregulated the extracellular acidification rate (ECAR) and oxygen consumption rate (OCR) values of activated CD4+ T cells from SS mice. In vivo, we injected different doses of BPTES into SS-like NOD/Ltj mice and found that 10 mg/kg BPTES significantly restored the salivary flow rate. Histological and qRT–PCR analyses showed that this concentration of BPTES attenuated lymphocytic infiltration and the numbers of PCNA-positive cells and CD4+ T cells. The proportions of IFNγ-producing cells and IL-17A-producing cells and the expression of several proinflammatory cytokines, including IFNγ and IL-17A, were also affected in the salivary glands of SS-like mice. Cytokine production in circulating serum was analyzed and showed that BPTES downregulated the effector functions of Th17 cells and Th1 cells. Collectively, these results indicate a positive relationship between Gls1 and SS development. Pharmacological inhibition of Gls1 with BPTES could normalize the effector functions of CD4+ T cells and effectively attenuate the symptoms of SS.